A fast inertial self-adaptive projection based algorithm for solving large-scale nonlinear monotone equations - Zhang, N.; Liu, J.K.; Zhang, L.Q.; Lu, Z.L. (Journal of computational and applied mathematics, 2023)
In this paper, we propose a fast inertial self-adaptive projection based algorithm for solving large-scale monotone equations with the relaxation factor. The modified hyperplane projection technique accelerates the computational performance of the proposed algorithm, and the self-adaptive parameter enhances its stability. Under some appropriate assumptions, the global convergence of the proposed algorithm is established. Moreover, the proposed algorithm is suitable to solve large-scale problems because it does not need gradient information or Jacobian matrix. The numerical results indicate that the new algorithm is robust and efficient by comparing with other popular algorithms.